Cover and Table of Content - AlphaMath: Journal of Mathematics Education (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
FOREWORDAssalamu’alaikum Wr. Wb. Praise the presence of Allah SWT for all the overflow of His Rahmat so that we can publish the journal AlphaMath volume eight number two. The creation of the journal AlphaMath aims to develop the writing culture of educators for both teachers and lecturers. In addition, the journal AlphaMath also seeks to accommodate all aspirations, ideas, and potentials related to the world of education. This journal's publication is in line with the vision and mission of the Mathematics Education Department Universitas Muhammadiyah Purwokerto. The concept and mission are superior in developing the education profession and mathematical competence.The scope of the material in this journal is related to the world of mathematics education. This is to obtain innovations in teaching and ideas from educators to disseminate. Hopefully, this journal will always be evaluated to improve its quality. In this issue, the journal AlphaMath features eleven articles related to model learning, mathematical ability, and ethnomathematics. The authors of the journal come from various educational institutions.Hopefully, this AlphaMath journal can provide benefits for readers and educational actors.Wassalamu’alaikum Wr. Wb.